Modeling the Effect of Chinese EFL Teachers’ Self-efficacy and Resilience on Their Work Engagement: A Structural Equation Modeling Analysis - Wang, Yongliang; Pan, Ziwen (SAGE open, 2023)
Teaching is deemed a taxing enterprise, especially as far as higher education is concerned. As a result, much research attention has been showered upon exploring the correlates of engagement for instructors. To contribute to this research direction, the present researchers carried out this survey to test a model of work engagement in a Chinese higher education context. Teacher self-efficacy and resilience were added as predictors of the hypothesized model. A number of 372 Chinese English as a foreign language (EFL) instructors in higher education contexts were selected through convenience sampling. The measurement models of the latent variables (i.e., self-efficacy, resilience, and work engagement) were confirmed via running Confirmatory Factor Analysis (CFA). Afterward, Structural Equation Modeling (SEM) was used to test the structural model. The results obtained from the analyses showed that both teacher self-efficacy and resilience could significantly predict EFL teachers’ work engagement, with self-efficacy serving as a stronger predictor than resilience. The outcomes suggest some implications for EFL stakeholders such as teachers, teacher trainers, policy makers, and officials. Plain Language Summary This new article bridges the identified gaps in the literature, and the current research intends to examine the predictability of EFL teachers work engagement level in terms of their self-efficacy beliefs and resilience tendencies. Based on our observation, there is a paucity in the literature examining the causal relationship between teacher self-efficacy and teacher work engagement in HE, and to our knowledge, this is the first study to consider teacher self-efficacy as a potential predictive variable of work engagement of EFL teachers in HE.